Therapeutic Irradiation: Consequences for Bone and Bone Marrow Adipose Tissue - Costa, Samantha; Reagan, Michaela R. (Frontiers in Endocrinology, 2019)
Radiotherapy continues to be one of the most accepted medical treatments for cancer. Localized irradiation is the most common treatment for prostate, pancreatic, rectal, cervical and endometrial malignancies. Conventional localized fractions are total doses of 30-62Gy at 1.8-2Gy per fraction, with administration of ~60Gy often used for tumor ablation. However, even the lowest dose of localized irradiation exposure can result in adverse complications to adjacent organs, tissues, and vessels, which absorb a portion of the treatment. Skeletal complications are common amongst cancer patients undergoing these localized treatments. Irradiation exposure causes deterioration to the overall quantity and quality of bone by interfering with the trabecular architecture through increased osteoclast activity and decreased osteoblast activity. Irradiation-induced bone damage parallels adipocyte infiltration of the bone marrow (BM) resulting in compositional alterations of the microenvironment that may further affect bone quality and disease state. There may also be direct effects of irradiation on the BM adipocyte/pre-adipocyte, although in vitro findings do not always agree and cellular response is dependent on irradiation dosage. Hematopoietic cells also become apoptotic upon irradiation, which causes a range of skeletal effects. Bone loss leaves patients at a greater risk for osteopenia, osteoporosis, osteonecrosis, and skeletal fractures that drastically reduce quality of life. Osteoanabolic agents stimulate bone formation and reduce fracture risk in patients with low bone density; thus, osteoanabolic or anti-resorptive agents may be useful co-treatments with irradiation. This review discusses these topics and proposes further research directions using novel or combination therapies to enhance bone health during irradiation.